Nanosystems for oxidative stress regulation in the anti-inflammatory therapy of acute kidney injury - Wang, Yue; Jiang, Hong; Zhang, Longyao; Yao, Peng; Wang, Shaoqing; Yang, Qian (Frontiers in Bioengineering and Biotechnology, 2023)
Acute kidney injury (AKI) is a clinical syndrome that results from a rapid decline in renal structure or renal functional impairment with the main pathological feature of sublethal and lethal damage to renal tubular cells. However, many potential therapeutic agents cannot achieve the desired therapeutic effect because of their poor pharmacokinetics and short retention time in the kidneys. With the recent emergence and progress of nanotechnology, nanodrugs with unique physicochemical properties could prolong circulation time, enhance efficient targeted delivery, and elevate the accumulation of therapeutics that can cross the glomerular filtration barrier and indicate comprehensive application prospects in the prevention and treatment of AKI. In this review, various types of nanosystems (such as liposomes, polymeric nanosystems, inorganic nanoparticles and cell-derived extracellular vesicles) are designed and applied to improve the pharmacokinetics of drug formation, which could further relieve the burden on the kidneys caused by the final cumulative dose of drugs in conventional treatments. Moreover, the passive or active targeting effect of nanosystems can also reduce the total therapeutic dose and off-target adverse effects on other organs. Nanodelivery systems for AKI management that alleviate oxidative stress-induced renal cell damage and regulate the inflammatory kidney microenvironment are summarized.